Impact of Non-Performing Loan and Macro-Economic Variables on Financial Performance of Commercial Banks in Nepal - Ranabhat, Santosh; Subedi, Raj Kumar (Journal of Interdisciplinary Studies, 2022)
This study aims to measure the impact of non-performing loan and macro-economic variables on financial performance of commercial banks in Nepal. The dependent variables are return on assets, return on equity and capital adequacy ratio which measure the financial performance and independent variables are NPL, GDP growth, inflation and interest rate measure the macro-economic variables. Primary and secondary data were collected through the structured questionnaire and annual reports of commercial banks and economic survey respectively. Convenience sampling was used to select the commercial banks located in Pokhara for collecting primary data of 80 respondents. Stratified simple random sampling was used to select 10 commercial banks (three JV and seven NJV banks) out of total population of 27 commercial banks for a time period of 2073/74 to 2077/78 for collecting secondary data. Multiple regression analysis, correlation analysis and descriptive statistics were used in analyzing the data. The primary data analysis concluded that most of the respondents have knowledge about the provision of non-performing loan according to NRB directives among bank staffs. The questionnaire survey shows majority of respondents agree with the statement macro-economic variables of non-performing loan affect the financial performance. The analysis of secondary data in correlation analysis reveals that the relationship between ROA, ROE and CAR with NPL is negative and insignificant. Similarly, the relationship between macro-economic variables with NPL is insignificant for JV and NJV banks. The relationship between ROA and ROE with GDP growth and interest rate is positive and significant for JV banks. The positive effect of GDP growth and interest rate on profitability indicates that increase in GDP growth and interest rate ultimately increases financial performance of JV banks. The regression analysis reveals that relationship between NPL with ROE is negative and significant for NJV bank which implies that increase in NPL decreases ROE. Likewise, this study also helps the future researchers to conduct future research on impact of NPL on firm performance to extend with new data and sample.